N-2 state population in Titan's atmosphere - Lavvas,P; Yelle,RV; Heays,AN; Campbell,L; Brunger,MJ; Galand,M; Vuitton,V (Icarus, 2015)
We present a detailed model for the vibrational population of all non pre-dissociating excited electronic states of N2, as well as for the ground and ionic states, in Titan’s atmosphere. Our model includes the detailed energy deposition calculations presented in the past (Lavvas, P. et al. [2011]. Icarus 213(1), 233–251) as well as the more recent developments in the high resolution N2 photo-absorption cross sections that allow us to calculate photo-excitation rates for different vibrational levels of singlet nitrogen states, and provide information for their pre-dissociation yields. In addition, we consider the effect of collisions and chemical reactions in the population of the different states. Our results demonstrate that above 600 km altitude, collisional processes are efficient only for a small sub-set of the excited states limited to the A and W(ν = 0) triplet states, and to a smaller degree to the a′ singlet state. In addition, we find that a significant population of vibrationally excited ground state N2 survives in Titan’s upper atmosphere. Our calculations demonstrate that this hot N2 population can improve the agreement between models and observations for the emission of the View the MathML source state that is significantly affected by resonant scattering. Moreover we discuss the potential implications of the vibrationally excited population on the ionospheric densities.